Biogenic platinum nanoparticles using black cumin seed and their potential usage as antimicrobial and anticancer agent - Aygun, Aysenur; Gülbagca, Fulya; Ozer, Lutfiye Yildiz; Ustaoglu, Buket; Altunoglu, Yasemin Celik; Baloglu, Mehmet Cengiz; Atalar, Mehmet Nuri; Alma, Mehmet Hakkı; Sen, Fatih (Elsevier BV, 2020)
Herein, the biogenic platinum nanoparticles (Pt NPs) were synthesized by using black cumin seed (Nigella sativa L.) extract as a reducing agent. The biogenic platinum nanoparticles synthesized by black cumin seed extract was characterized in detail by Transmission Electron Microscopy (TEM), UV-vis spectrophotometer, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS). According to TEM analysis, Pt nanoparticles have spherical shapes and sizes between 1-6 nm. Moreover, the biogenic Pt NPs was assessed for its cytotoxicity effect on MDA-MB-231 breast and HeLa cervical cancer lines and their antibacterial effect against selected strains of gram-positive and negative bacteria. The cytotoxicity and bacterial tests showed the effectiveness of biogenic Pt nanoparticles. Dose-dependent toxicity effects were shown in the MDA-MB-231 breast and HeLa cervical cancer lines (IC50: 36.86 μg/mL and 19.83 μg/mL, respectively). In addition, Pt NPs showed high zone diameters against gram-positive and gram-negative bacteria at concentrations of 100 and 500 μg/ml. These results contribute to the development of the pharmaceutical industry as a potential antibacterial and anticancer agent.
Keywords: MDA-MB-231; Metal Nanoparticles; Uterine Cervical Neoplasms; Breast Neoplasms; Gram-Positive Bacteria; Inhibitory Concentration 50; Cell Line, Tumor; Gram-Negative Bacteria; Humans; Nigella sativa; Platinum; Dose-Response Relationship, Drug; Plant Extracts; Antineoplastic Agents, Phytogenic; Anti-Bacterial Agents; Antibacterial; Anticancer; Seeds; HeLa Cervical Cancer Lines; Female; Nigella Sativa L.; Biogenic Platinum Nanoparticles; HeLa Cells; 3. Good health